Trends in Stunting Prevalence in East Java (2019-2023): A Comprehensive Analysis - Hasan, Diana Sukmawati (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2024)
This study aims to analyze the trends in stunting prevalence in East Java from 2019 to 2023. Using a quantitative approach, secondary data from the Monitoring Implementation of the Eight Convergence Actions for Integrated Stunting Reduction Interventions, provided by the Directorate General of Regional Development at the Ministry of Home Affairs, was employed. A descriptive quantitative analysis was conducted to interpret the data. The findings reveal a significant decline in stunting prevalence, particularly from 2021 onwards, highlighting the effectiveness of targeted interventions. Despite ongoing challenges in districts such as Pasuruan and Batu, which still report high stunting rates, the overall stunting prevalence in East Java decreased notably, from 11.5% in 2019 and 2020 to 6.9% in 2023. Urban areas like Surabaya and Mojokerto demonstrated the lowest stunting rates, offering evidence of the success of integrated strategies. These results emphasize the need to maintain and expand stunting reduction efforts, particularly in regions with persistently high rates. Policymakers are encouraged to tailor interventions based on regional needs, leveraging successful strategies from areas with low stunting prevalence. Additionally, cross-sectoral collaboration, including enhanced access to healthcare, nutrition, and early childhood development programs, is essential to sustaining recent progress